Application Of Lights in The Nursery of Snubnose Pompano Trachinotus blochii (Lacepède, 1801) In Ponds as An Effort to Increase Feed Cost Efficiency - Wahyudi, Dzikri; Mardjoko, Mardjoko; Nawir, Fitria; Garnawansah, Gagan; Waluyo, Waluyo; Hidayati, Sri; Nugraha, Muhammad Ar Rozzaaq (Journal of Aquaculture and Fish Health, 2024)
The snubnose pompano (Trachinotus blochii), which is an introduced fish, is currently in increasing demand, both for the domestic market (Jakarta and other big cities) and international markets such as Singapore, Taiwan, Hong Kong, and China. The snubnose pompano can be cultivated in ponds because it is tolerant to changes in salinity (5-40 ppt). In this study, the use of lights installed in cages used to maintain the snubnose pompano nursery will be responded to natural food that is positively phototactic (zooplankton, shrimp, and small fish species) which will gather as feed at night. So, it is hoped that the use of these organisms as an alternative feed source can increase feed efficiency. The urgency of this research is to determine efforts to save on the use of artificial feed and to suppress parasite attacks. A t-test was carried out to compare the averages of two different samples, on the growth rate and health of snubnose pompano fish. Research using lights resulted in optimum growth of snubnose pompano with 100% survival rate, feed conversion ratio (FCR) value of 0.9 and produced snubnose pompano size 80–100 g/head within two months as well as healthy fish seeds. With indicators of parasitic attack that are lower than the treatment without light with a prevalence value of 25% (with lights); range of 25%-75% (without lights) and intensity 6-8 (with lights); range 11-35.67 (without light). The snubnose pompano seeds are always actively moving when the light is on, the use of the light can effectively catch organisms such as small shrimp or small crustaceans so that the snubnose pompano seeds can be used to be digested as an alternative food (as observed in the stomach contents and intestines of the snubnose pompano). The light also indicates that parasitic attacks on the snubnose pompano are less common.